2021
DOI: 10.3390/jcm10040753
|View full text |Cite
|
Sign up to set email alerts
|

Transanal Irrigation for Neurogenic Bowel Disease, Low Anterior Resection Syndrome, Faecal Incontinence and Chronic Constipation: A Systematic Review

Abstract: Transanal irrigation (TAI) has received increasing attention as a treatment option in patients with bowel dysfunction. This systematic review was conducted according to the PRISMA guidelines and evaluates the effect of TAI in neurogenic bowel dysfunction (NBD), low anterior resection syndrome (LARS), faecal incontinence (FI) and chronic constipation (CC). The primary outcome was the effect of TAI on bowel function. Secondary outcomes included details on TAI, quality of life (QoL), the discontinuation rate, adv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(22 citation statements)
references
References 62 publications
(434 reference statements)
2
18
1
1
Order By: Relevance
“…Most published studies analyze the efficacy of TAI simultaneously on FI and CC [31]. Alterations in lifestyle, coping, depression, social isolation and embarrassment are the fundamental elements lowering the QoL of patients suffering from FI [32].…”
Section: Literature Resultsmentioning
confidence: 99%
“…Most published studies analyze the efficacy of TAI simultaneously on FI and CC [31]. Alterations in lifestyle, coping, depression, social isolation and embarrassment are the fundamental elements lowering the QoL of patients suffering from FI [32].…”
Section: Literature Resultsmentioning
confidence: 99%
“…A recent pilot study in rectal cancer patients after SPS reported that standardized interventions for bowel dysfunction led by trained personnel in specialized clinics may successfully ameliorate symptoms ( 24 ). Additionally, transanal irrigation has been receiving increased attention as a treatment option in patients with bowel dysfunction following SPS ( 25 ). These efforts may result in improvements in QOL after SPS and are important areas for future research.…”
Section: Discussionmentioning
confidence: 99%
“…TAI has been gaining acceptance as a treatment option for different bowel dysfunctions such as neurogenic disorders, chronic constipation, faecal incontinence and low anterior resection syndrome. It has been demonstrated to be an inexpensive and effective technique, comparing with conservative management and other not invasive therapies such as tibial nerve stimulation 1 . Minor side effects include cramps, bloating, nausea and anorectal pain or bleeding.…”
Section: Figmentioning
confidence: 99%
“…It has been demonstrated to be an inexpensive and effective technique, comparing with conservative management and other not invasive therapies such as tibial nerve stimulation. 1 Minor side effects include cramps, bloating, nausea and anorectal pain or bleeding. Nevertheless, serious complications have been reported, as well: 49 cases of bowel perforation of which 35 with Peristeen system 2 and one case of colo-vaginal fistula.…”
mentioning
confidence: 99%